Immunophenotyping of peripheral circulating lymphocytes and serum selenium levels in calves with neonatal diarrhea - Uztimuer, Murat; Kizil, Omer; Akbulut, Hatice Handan (Elsevier, 2024)
This work aims to: (1) elucidate the immune response exhibited by CD4 + and CD8 + T lymphocyte cells in response to various infectious agents in calves suffering with neonatal diarrhea; and (2) determine and investigate the association between serum selenium levels and T lymphocyte subtypes in neonatal calves afflicted with neonatal diarrhea and infected with various infectious agents. The study encompassed a cohort of 50 calves, encompassing both sexes and various breeds, within the neonatal age range (1-28 days old). Subdivided into distinct groups, the calves were categorized based on the causative agents of neonatal diarrhea, including Rotavirus (n = 10), Cryptosporidium parvum (C.parvum) (n = 10), Coronavirus (n = 5), Rotavirus+C.parvum (n = 5), and a Control group (n = 20). Blood samples were meticulously obtained from the vena jugularis of all animals utilizing specific techniques-8 ml in tubes devoid of anticoagulant and 3 ml in blood collection tubes containing EDTA. Serum selenium levels were analyzed by ICP-MS. Flow Cytometry device was used to determine CD4 + and CD8 +T lymphocyte levels. In this study, although there was no statistically significant difference in serum selenium levels between all study groups, it was found that the selenium level in the control group was not sufficient. CD4 T lymphocyte levels, the rotavirus+C.parvum group exhibited a statistically significant elevation compared to the coronavirus group. Regarding CD8 + T lymphocyte levels, the coronavirus group demonstrated a statistically significant increase when compared to the control group. In intragroup analyses of CD8 + T lymphocyte levels, the coronavirus group exhibited a significant elevation compared to the rotavirus group, C.parvum group, and the C.parvum + Rotavirus group. A significant negative correlation was detected between selenium levels and CD4 + T lymphocytes, while no correlation was found between CD8 + T lymphocytes. Fibrinogen concentration exhibited statistical significance, being higher in the Rotavirus group (p < 0.008) compared to the control group, in the C.parvum group (p < 0.004) compared to the control group, and in the Coronavirus group (p < 0.001) compared to the control group. The leukocyte count demonstrated statistical significance, being higher in the Rotavirus group compared to the control group (p < 0.001), in the Rotavirus+C.parvum group compared to the control group (p < 0.002), and in the Coronavirus group compared to the control group (p < 0.011). In conclusion, the data derived from this study illuminate discernible disparities in CD4 + and CD8 + T lymphocyte immune responses, contingent upon the specific etiological agent associated with neonatal diarrhea. Furthermore, the study underscores the importance of considering selenium deficiency as a relevant factor in calves affected by neonatal diarrhea.
Keywords: CD4+; CD8+; Calf diarrhea; Selenium; And Flow cytometry